Beyond the everyday? Rethinking place meanings in tourism. Issue 1 (1st January 2017) - Chen, Jingfu; Chen, Ningning
ABSTRACT: Existing tourism scholarship on place meanings seems to retain an underlying assumption of a contradiction between tourist places and the mundane world. In contrast, this paper contends that the production of the meanings of tourist places is also closely related to everyday life. To make its case, it interrogates the creation of meanings of two scenic sites of Tianya Haijiao and Nanshan in Sanya, a famous coastal destination in southern China. Although both scenic sites have been recently developed, their significance stems from historical and cultural meanings in traditional Chinese culture, which are frequently communicated in people's daily conversations and practices. Besides, the meanings of the tourist sites are neither fixed by legitimate discourses nor dominated by tourism publicity; they are continuously shaped by wider socio-spatial events in mundane societies and re-interpreted through tourism mobilities in accordance with tourists' everyday concerns. This paper echoes the 'new mobilities turn' in tourism studies and contributes to the discussions of the mundaneness of tourist places.